DIGITALISASI PELAYANAN PUBLIK DI DINAS KEPEDUDUKAN DAN PENCATATAN SIPIL KOTA PALEMBANG - Fahlevi, A Rizal; Ellyza (Lentera Jurnal Manajemen, 2024)
Abstract In this era of increasingly advanced technology, the government is required to innovate in providing services to the public. One form of innovation can be carried out in the implementation of e-government. Its implementation utilizes technology and needs to be supported by the availability of adequate infrastructure and human resources. Indonesia has initiated a policy of utilizing ICT to build an integrated Electronic Government for Good Governance from regional to central government. The purpose of this research is to determine the digitalization of public services in the Palembang City Population and Civil Registration Service. The method used in this research is a descriptive qualitative method. Data was obtained from interviews, field notes, and documentation, both documents obtained online and obtained directly from informants. The data collection technique was carried out by triangulation. The results of this research found that services at the Palembang City Population and Civil Registration Service were divided into 9 (nine) UPTs and services were transferred to online services so that population administration services were more effective and efficient, however, the Palembang City Population and Civil Registration Service had limited personnel in carrying out their duties. Population administration data management is not yet fully professional, this is because the number of officers and population data is not balanced. This can be seen from the population data obtained which is quite large but the number of officers is limited so that the data input time is not fast and does not match the predetermined time.